2006
DOI: 10.1111/j.1365-2311.2006.00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Limitation of nesting resources for ants in Colombian forests and coffee plantations

Abstract: 1. This study examines limitation of nesting resources for leaf-litter and twig-nesting ants as a mechanism of diversity loss across an intensification gradient of coffee production in Colombia. Twelve farms were selected and classified into four management types: forest, polygeneric shade coffee, monogeneric shade coffee, and sun coffee (unshaded coffee monocultures).2. At each of the farms, four treatment subplots were established at the corners of each of 10 25 m 2 plots: (i) twig augmentation (adding 10 em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 30 publications
1
23
0
6
Order By: Relevance
“…Thus, it is difficult to say that differences in nest limitation are due to the agroecological context, as previous studies in coffee plantations have found that the community of twig‐nesting ants are limited by nesting resources (Armbrecht et al. ), as are ants in natural ecosystems (Kaspari ; Powell et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is difficult to say that differences in nest limitation are due to the agroecological context, as previous studies in coffee plantations have found that the community of twig‐nesting ants are limited by nesting resources (Armbrecht et al. ), as are ants in natural ecosystems (Kaspari ; Powell et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially the case for ant communities, in which inter-specific competition is important and numerical dominance enables resource acquisition ( Palmer, 2003 ). Differences in ant abundance between sites may be driven by a variety of biotic and abiotic factors, including nest availability ( Hölldobler & Wilson, 1990 ;Armbrecht et al , 2006 ), microhabitat variation ( Palmer, 2003 ), differences in vegetation ( Ribas et al , 2003 ), and other food resources ( Sanders & Gordon, 2003 ). Differences in ant abundance between sites may be driven by a variety of biotic and abiotic factors, including nest availability ( Hölldobler & Wilson, 1990 ;Armbrecht et al , 2006 ), microhabitat variation ( Palmer, 2003 ), differences in vegetation ( Ribas et al , 2003 ), and other food resources ( Sanders & Gordon, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, agricultural landscapes where small-scale farming is significant have been noted for their potential for tree (Lengkeek et al, 2006;Kindt et al, 2007), soil biota (Barrios et al, 2012), bird (Komar, 2006), insect (Armbrecht et al, 2006;Perfecto et al, 1996), mammal (Gallina et al, 1996), and orchid (Solis-Montero et al, 2005) biodiversity conservation in the tropics.…”
Section: Introductionmentioning
confidence: 99%